Pulmonary artery capacitance a simple and novel prognostic variable in acute pulmonary embolism. (14th October 2021) - Quintero-Martinez, J A; Cordova, S N; Alam, M M; Jain, V; Vlazny, D T; Houghton, D E; Casanegra, A I; Wysokinski, W E; Villarraga, H R
Abstract: Background: The non-invasive calculation of right ventricular hemodynamics such as the pulmonary artery capacitance (PAC) has proven to be feasible and easy to perform. The simplified pulmonary embolism severity index (sPESI) and pulmonary vascular resistance (PVR) are other prognostic tools that have been used in the past. Purpose: To evaluate if baseline PAC can outperform PVR and sPESI to predict all-cause short-term mortality in patients with acute pulmonary embolism (PE). Methods: 373 patients with acute PE and a transthoracic echocardiogram performed within one day of diagnosis from March 2013 through June 2020 were followed prospectively. PAC was calculated as: Left ventricular stroke volume/ (Pulmonary artery systolic pressure – Pulmonary artery diastolic pressure). PVR was calculated as: Tricuspid regurgitant velocity / Right ventricular outflow tract velocity time integral x 10 + 0.16. The sPESI was used to evaluate prognosis by categorizing patients into low and high-risk categories. Multiple logistic regression analyses and receiver-operating characteristic curves were used to evaluate the ability of PAC, PVR, and sPESI to predict all-cause mortality up to six months. The Youden index was used to determine the cut-off value with the highest sensitivity and specificity. Kaplan–Meier curves were performed to determine event-free survival rate, differences between groups were assessed using the Wilcoxon Test. Results: Mean age was 64±15 years (58% male, 28% cancer). PAC was associated with mortality at thirty days (p 0.0003), three months (p 0.003), and six months (p 0.011) (Table). PVR was associated with mortality at thirty days, three months, and six months (p 0.045, 0.012, and 0.031 respectively). The sPESI score ≥1 (high risk) was associated with all-cause mortality at three months and six months (p 0.0136 and <0.0001 respectively). PAC was the strongest predictor of all-cause mortality with an AUC of 0.95 (CI 0.82- 0.99) at thirty days, 0.84 (CI 0.65–0.99) at three months, and 0.77 (CI 0.57–0.96) for six months. Corresponding Kaplan-Meier survival curve of PAC and thirty days all-cause mortality is presented in the Figure. PVR had an AUC of 0.75 (CI 0.48–0.95) at thirty days, 0.79 (CI 0.58–0.94) at three months, and 0.72 (CI 0.50–0.90) at six months. The sPESI had an AUC of 0.62 (CI 0.54–0.66) at three months and 0.64 (CI 0.59–0.67) at six months. Conclusion: In patients with acute PE, PAC outperforms sPESI and PVR as a predictor of short-term all-cause mortality at thirty days, three months, and six months. These three variables should be explored head to head prospectively for their utility to predict short term all-cause mortality. Funding Acknowledgement: Type of funding sources: None.